Development of E-Module in Problem-Based Learning (PBL) on Biotechnology Material to Increase Learning Independence and Understanding of Concepts for Class XII SMA Students - Ratna Dewi; Ixora Sartika Mercuriani (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this study are determine the feasibility of developing an e-module in problem-based learning (PBL) with the flipped classroom learning method on biotechnology material to increase students' learning independence and understanding of concepts; determine the practicality of developing e-modules in problem-based learning (PBL) using the flipped classroom learning method for biotechnology material to increase students' learning independence and understanding of concepts; determine the effectiveness of e-module development in problem-based learning (PBL) using the flipped classroom learning method for biotechnology material to increase students' learning independence and understanding of concepts. The results of this research indicate that the e-module in problem-based learning (PBL) with the flipped classroom learning method is stated: very suitable for use based on the assessment of material experts with a value of 3.8 conversion 95 with a very feasible category and the assessment of media experts with a value 4.00 100 conversions with very decent category; very practical to use based on the results of the Biology Teacher's assessment with a score of 4.00 conversion 100 in the very feasible category and student assessment with a score of 3.87 conversion 97 in the very practical category; is effectively used to increase learning independence and conceptual understanding of phase F students based on the MANOVA test p < 0.05. The development of an e-module in problem-based learning (PBL) using the flipped classroom learning method on biotechnology material is feasible, practical and effective to use.